ANALYZING STUDENTS MATHEMATICS LEARNING DIFFICULTIES IN THE MATTERIALS OF LINEAR EQUATION SYSTEM WITH TWO VARIABLES IN GRADE VIII OF SMP MUHAMMADIYAH 1 PRAMBANAN SLEMAN REGENCY IN THE ACADEMIC YEAR OF 2018/2019 - Yayang Suci Mariya Dalyanti; Sunaryo Sunaryo (Universitas Ahmad Dahlan, 2022)
Mathematics learning difficulties are commonly faced by the students of SMP Muhammadiyah 1 Prambanan in the Materials of Linear Equation System with Two Variables. This study aims to determine the students’ mathematics learning difficulties in the Materials of Linear Equation System with Two Variables (SPLDV) in SMP Muhammadiyah 1 Prambanan seen from the factual, conceptual, and procedural difficulties. The research sucject were grade VIII C students of SMP Muhammadiyah 1 Prambanan in the academic year of 2018/2019. The object of this research is the difficulties of learning mathematics in the Materials of Linear Equation System with Two Variables. The data were collected through test, interview guidelines, and image recording. The data were analyzed using Miles and Hubberman model steps which include (1) data reduction (2) data display (3) verification. The results showed that the students found difficulties in learning the Materials of Linear Equation System with Two Variables (SPLDV), with the average score for factual difficulties were 52%, conceptual difficulties 63%, and procedural difficulties 64%. Students experience factual difficulties due to lack of understanding of the problems so they cannot change into mathematical sentences. Whereas students who experience conceptual difficulties because they cannot use the rules equate one variable coefficient. As for procedural difficulties because students do not write the steps to work correctly, so the results are less precise.